Sudden improvement in ventricular repolarization abnormality after a short detraining period in an athlete. (27th June 2017) - Motoki, Noriko; Akazawa, Yohei; Hachiya, Akira; Inaba, Yuji
Abstract: We describe the case of a 17-year-old male soccer player with T-wave inversion in precordial leads in resting electrocardiography, which also disclosed sinus bradycardia, early repolarization, and increased QRS voltage. These findings strongly suggested cardiomyopathy. The patient's T-wave inversion disappeared during only 2 weeks of detraining, and it re-appeared 2 weeks after resumption of intensive training. This sudden change in electrocardiographic parameters over a short period helped in identifying the adolescent as having athlete's heart.